Perancangan Aplikasi Survei Kepuasan Pengguna Layanan Pengadilan - Galih Ashari Rakhmat (Universitas Budi Darma, 2021)
Information technology has become a major need in everyday life, not only used by individuals but also by a group or organization. Information technology makes all activities more efficient in terms of energy, time and cost. Therefore, the Bandung District Court Class 1A Special participates in utilizing information technology, with the One Stop Integrated Service (PTSP) and Case Search Information System (SIPP) service activities are increasingly efficient in terms of time and cost. However, not all PTSP and SIPP users at the Bandung District Court understand how to use them, so a court service user satisfaction survey is provided to find out whether the performance of the employees is as desired or not. However, the survey tools available at the Bandung District Court Class 1A Special are still in the form of a manual survey box that requires energy and time in processing the data. The results obtained with the development of an information system for this service user satisfaction survey are that the assessment of service users towards each clerk can be known clearly and precisely, besides that the processing of survey reports is more efficient in terms of time and effort, because officers do not need to calculate or manually processing survey data.